Aplikasi Sistem Informasi Jasa Make Up Berbasis Web Pada Studi Kasus IYAIYOH Make Up - Muhammad Fatchan; Rohayati Rohayati (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
Make Up Artists (MUA) usually offer their services using social media such as Facebook and Instagram. However, through the media, it is still not optimal because it is difficult for customers to know the location and whether the make-up service can come directly to the customer's place or not. In the ordering process, lyaiyoh Make Up is still done manually, that is, it is recorded in a book and the customer must contact by telephone or come directly to the salon to place an order. The purpose of this research is to design a web-based make-up service information system that was built using the Waterfall method. The benefits of this research are making it easier to register and ordering for customers, more structured and directed data management so as to minimize errors in recording. The conclusion is that in addition to the data processing process that becomes computerized, this system can also be a promotional media for lyaiyoh Make Up services